Vitamin A supplementation enhances Senegalese sole (Solea senegalensis) early juvenile's immunocompetence: New insights on potential underlying pathways. Issue 2 (October 2015) - Fernández, Ignacio; López-Joven, Carmen; Andree, Karl B.; Roque, Ana; Gisbert, Enric
Abstract Senegalese sole (Solea senegalensis) has been considered since the 1990's to be a promising flatfish species for diversifying European marine aquaculture. However, pathogen outbreaks leading to high mortality rates can impair Senegalese sole commercial production at the weaning phase. Different approaches have been shown to improve fish immunocompetence; with this in mind the objective of the work described herein was to determine whether increased levels of dietary vitamin A (VA) improve the immune response in early juveniles of Senegalese sole. For this purpose, Senegalese sole were reared and fed with Artemia metanauplii containing increased levels of VA (37, 000; 44, 666; 82, 666 and 203, 000 total VA IU Kg−1) from 6 to 60 days post-hatch (early juvenile stage). After an induced bacterial infection with a 50% lethal dose of Photobacterium damselae subsp. damselae, survival rate, as well as underlying gene expression of specific immune markers (C1inh, C3, C9, Lgals1, Hamp, LysC, Prdx1, Steap4 and Transf) were evaluated. Results showed that fish fed higher doses of dietary VA were more resistant to the bacterial challenge. The lower mortality was found to be related with differential expression of genes involved in the complement system and iron availability. We suggest that feeding metamorphosed Senegalese sole with 203, 000 total VA IU Kg−1 might be an effective, inexpensive and environmentally friendly method to improve Senegalese sole immunocompetence, thereby improving survival of juveniles and reducing economic losses.